Viajando entre sereias: saúde de transexuais e travestis na cidade de Fortaleza - Sampaio, Juliana Vieira (2014)
The aim of this study was to investigate practices that transvestites and transsexuals in Fortaleza (Ceará-Brazil) use to produce health and how they relate to institutionalized knowledge in this field. Health in Brazil is duty of the state and fundamental right of the population since 1990, when the Unified Health System (Sistema Único de Saúde SUS) was created. Despite being a universal right some studies indicate a process of exclusion of trans people from health services due to the prejudice they suffer in those places. We began our research by exploratory visits to health facilities indicated as references in the care of transvestites and transsexuals in Fortaleza, which were registered in a field diary. We observed that the heteronormative sexual norm based on binary gender usually organizes the actions of the public health service when the focus is this population. There is re-pathologization of non-heterosexual sexualities when the services directed to STD/aids and involved in transsexuality process become the main institutionalized spaces for the health of trans people. After initial exploratory visits we talked to transvestites and transsexuals because we believe that health cannot be reduced to a simple problem of state management, since health pervades all space and relationships. We conducted semi-structured research interviews with four transvestites and transsexuals and also had informal conversations in the spaces visited during research. This material was analyzed in Foucauldian perspective of discursive practices, that is, a set of anonymous rules located in time and space that produce conditions for exercising the enunciative function. From the reports of our trans interviewees we observe how they deal with the institutionalized spaces of health and which practices are selected as producers of health for this population. The disrespect towards the use of social name was one of the main complaints about the care in health facilities, lending them to alternative care at private clinics or emergency services. We observed that the production of trans health is generally associated with the construction of a beautiful female body and the utilization of several technologies, which are often identified by the official discourse of health as producers of disease, such as the use of silicone industrial and self-medication of hormones. We conclude that the main demand of health transvestites and transsexuals, the construction of a beautiful female body, is far from the way the State has acted to assist this population. Among other reasons this distance is produced as the result of the adoption of a binary and heteronormative notion of sex and gender by the State, which ends up excluding the bodies that escape and subvert the sexual norm.